Effect of scenario-supported training on pediatric nurses' knowledge and skills in extravasation and infiltration management - Uyar, Emel; Delibalta, Bilge; Ozyurt, Nese (Frontiers in Pediatrics, 2026)
BackgroundExtravasation and infiltration are preventable complications of intravenous therapy that can cause severe tissue injury in pediatric patients. Nurses play a critical role in prevention and early management, yet studies have shown that their knowledge and skills in this area are often insufficient. Simulation-based training has been shown to improve clinical competence; however, evidence specific to pediatric extravasation management is limited.MethodsThis quasi-experimental study employed a single-group pretest–posttest design. A total of 475 pediatric nurses were invited, 436 participated, and 399 were included in the final analysis after missing data excluded. A half-day, scenario-supported training program was developed by expert clinicians, combining theoretical lectures with low-fidelity, case-based simulation activities. Pre- and post-training scores were compared using nonparametric tests, with significance set at p < 0.05 and effect sizes reported. Knowledge was assessed using a validated 55-item test, and skills were measured through a four-station ObjectiveStructured Practical Examination (OSPE).ResultsParticipants were predominantly female (84.7%) and held a bachelor's degree (87.5%). The majority (77.9%) had never received prior extravasation training, while 88.5% expressed a need for education. Knowledge scores improved significantly post-training (p < 0.001, r = –0.26, small effect). Skill scores showed a marked improvement (p < 0.001, r = –0.84, large effect). Subgroup analyses revealed no significant differences by gender or educational level. Nurses with 5–8 years of experience demonstrated greater knowledge gains, while those with prior training achieved higher skill improvements.ConclusionScenario-supported training effectively improved pediatric nurses' competencies in extravasation and infiltration management, with the strongest effect observed in clinical skills. These findings underscore the importance of structured and repeated training, particularly for early- and mid-career nurses. Low-cost, scalable training models represent a practical and sustainable strategy to strengthen pediatric nursing practice and enhance patient safety in diverse healthcare settings.